On conditionally pathogenic microflora of caspian seal ( Phoca caspica) - Victoria V. Volodina (Известия ТИНРО, 2015)
Caspian seal was subjected in the 2000s to complex combined infection caused by viruses and pathogenic bacteria that led to mass mortality of this species, the only marine mammal in the Caspian Sea. So, bacteriological monitoring and detection of pathogenic microorganisms in internals and tissues of the seal were conducted in the 2007-2014 and a broad spectrum of high-adaptive pathogenic microbial associations was found. The examined mammals had not diseases of bacterial origin in that time, and the most part of this microflora was qualified as the resident one, but these bacteria were able to trigger infectious process in case of deterioration of environmental conditions (anthropogenic pollution, malnutrition, lack of ice fields, etc.). Composition and abundance of the conditionally pathogenic microflora depended on physiological state of seals: the animals with invasive diseases had more abundant and diverse sanitary-indicative microorganisms. Presence of highly adaptive opportunistic microorganisms in the organism of seal is a sign of unfavourable sanitary-microbiological state of this species and considerable persistence of sanitary-indicative microflora in the ecosystem of the Volga-Caspian basin, with significant parasitizing and multiple antibiotic resistance, that is a background for high epidemiological risk.